5n+6n-2n can be solved by combining like terms. Combine 5n and 6n and -2n to get 9n.
-6n-2n 16 can be solved mathematically getting n = - 2.
Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.
The answer is: n=4.
Let 2n be the first integer, then the next on is 2n+2 and the one after is 2n+4 so adding all three we have 6n+6=108 or 6n=102 and we want 2n so divide we divide 6n by 3 and we have 2n=34, and 2n+2=36 and lastly 2n+4=38 so 34, 36, 38 are the even integers we seek.
5n + 6n - 2n
5n+6n-2n can be solved by combining like terms. Combine 5n and 6n and -2n to get 9n.
5n+6n-2n can be solved by combining like terms. Combine 5n and 6n and -2n to get 9n.
If: -6n-2n = 16 Then: n = -2
15/6n + 6/6n = 21/6n = 7/2n
6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3
-6n-2n 16 can be solved mathematically getting n = - 2.
Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.
The answer is: n=4.
First we must collect and simplify 'like terms' 2n-6n-36. 2n-6n = -4n Therefore, -4n-36 Take out the greatest common factor. -4 (n+9) Ans = -4 (n+9)
Let 2n be the first integer, then the next on is 2n+2 and the one after is 2n+4 so adding all three we have 6n+6=108 or 6n=102 and we want 2n so divide we divide 6n by 3 and we have 2n=34, and 2n+2=36 and lastly 2n+4=38 so 34, 36, 38 are the even integers we seek.
The expression 2n times 3n can be simplified by multiplying the coefficients (2 and 3) to get 6, and multiplying the variables (n and n) to get n^2. Therefore, 2n times 3n simplifies to 6n^2. This represents the product of 2n and 3n in algebraic terms.